THE EFFECT OF IMPLEMENTATION PREVENTIVE MAINTENANCE SYSTEM AND THE VALUES OF AVAILABILITY, PERFORMANCE AND QUALITY TOWARDS OVERALL EQUIPMENT EFFECTIVENESS (Case Study in PT. Astra Honda Motor) - Dicky Kurniawan (Universitas Trisakti, 2012)
The background of this research refers to many companies that cannot identify about the system effect and overall equipment effectiveness (OEE) values, and cannot implement the right system continuously. So that, this research is to investigate some factors that influence the OEE values. The objective of this research were to investigate the effects of preventive maintenance to OEE and to decide whether of availability, performance, quality that most contribute to OEE values at PT. Astra Honda Motor. The design of this research applies case study to examine all hypothesis in this study. The methods used in this study was simple and multiple regression between independent variables and dependent variable. Data analysis used in this research were collected from preventive maintenance activity data and machining crank case production data. There were 91 average data of preventive maintenance activity and usable for analyzed by simple regression and 578 average data of machining crank case production completed and usable for analyzed by multiple regression. The result of research indicated that the first, preventive maintenance has no significant impact to OEE values. The second, availability give more contribution to OEE values than performance and quality.